Case Report: Postoperative Complication Epidural Haematoma after Brain Tumor Resection - Sikumbang, Kenanga Marwan; Juniarti, Ayu; Febria, Aswin; Susatya, Arif Budiman; Susianto, Oky (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2024)
Postoperative intracranial haemorrhage is one of the most dangerous complications in cranial surgery, especially epidural haematoma although it is very rare with an incidence of 1.0%. The exact mechanism of occurrence is still unknown and with appropriate treatment can result in a good outcome. A 34-year-old female, 63 kg, who lost consciousness after extubation following resection of a meningioma in the parietooccipital region. In the recovery room, the patient regained consciousness and was transferred to the ICU for observation. The patient suddenly lost consciousness after 30 minutes in the ICU, reintubation was performed and a CT scan of the head showed an epidural hematoma after tumour resection. An emergency decompressive craniotomy was performed, with total intravenous anaesthesia (TIVA) combination of remifentanil 0.1 mcg/kg/min and thiopental 2 mg/kg/h, The operation lasted for one hour. The patient was admitted to the intensive care unit (ICU) for seven days under mechanical ventilation. The patient was extubated on the eighth day and transferred to the ward on the following day. There are several causes of epidural hematoma after brain tumour resection, namely sudden decrease in ICP, massive CSF drainage, uneven ICP distribution, coagulopathy factors, and excessive pin fixation. Excessive loss of CSF during surgery causes displacement of the brain and creates negative pressure in the remote area. In this case, it is suspected that the sudden decrease in ICP caused traction on the meningeal blood vessels, so that the negative pressure made the dura pulled and caused extradural haematoma. Conclusion: Postoperative epidural haematoma is a serious and relatively rare complication but if treated promptly, will result in a favourable outcome.